Perlindungan Data Pribadi Nasabah dalam Perspektif Hukum Perbankan Syariah di Palangka Raya - Yutika Ariani Tungga Dewi; Andika Wijaya; Nuraliah Ali; Ivans Januardy (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The protection of customer personal data, security mechanisms and legal remedies for customers who suffer losses at Bank Syariah Indonesia, Palangka Raya Branch, are essential aspects in ensuring the security of digital banking services. This research employs an empirical legal method with a sociological approach through interviews and the examination of statutory regulations. The findings reveal that Bank Syariah Indonesia, Palangka Raya Branch, has implemented personal data protection in accordance with applicable legal provisions through the application of standard operating procedures, information technology security systems and restrictions on access to customer data. However, the losses experienced by customers in the examined case resulted from the customers’ own negligence in maintaining the confidentiality of their personal data; therefore, the bank could not be held legally liable. As a contribution of this study, preventive and repressive legal measures are proposed, including improving digital security education for customers, strengthening the bank’s internal supervision system and optimizing the implementation of personal data protection in digital banking services.